Processor-in-the-loop simulation of DSP based controller implemented in a PV micro-grid - Zaw, Nyi Thu (2016)
Demand for alternative energy source such as renewable energy industries are rising to strengthen energy security. Stability and power quality from renewable sources such as Photovoltaic Cells are greatly depending on converter’s controller design. In this project, processor-in-the-loop (PIL) controller method in micro-grid is used as an approach to analyze simulation characteristics and stability of the micro-grid. Moreover, V-I characteristics of the photovoltaic cell and maximum power point tracking algorithm (MPPT) is implemented using C-script block in PLECS software. Multilevel neutral point clamped converter is also implemented as DC-AC converter for PIL micro-grid simulation. Performance of MPPT algorithm and simulation characteristics for micro-grid system are analyzed for verification and further improvements.